KRITIK TEKS ATAS LUKAS 4:4: "ADA TERTULIS: MANUSIA HIDUP BUKAN DARI ROTI SAJA.” - Ngoranubun, Willem; Luturmas, Johanis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
The purpose of this study is to trace the sources of Luke 4:4 and its variants in order to provide a relevant explanation for believers in interpreting Luke 4:4. The research method used in this paper is the library research. This research examines more on old literature that contains relevant studies, namely early text, original or oldest text that became the source of writing the Scriptures. In particular, this research attends the stages of biblical text criticism which includes four stages, namely verbal criticism, external criticism, internal criticism, and rational criticism. This research finds that the short version of Luke 4:4 is really the writing of the evangelist Luke. It is sourced from the oldest manuscript in 253 fromOrigenes and several well-known manuscripts such as ℵ 01 or Codex Sinaiticus (4th century), B 03 orCodex Vaticanus (4th century) and W 032 or Codex Washingtonianus (5th century). The research alsodiscovers that scribes intentionally create variants of Luke 4:4 are similar to Matthew 4:4 to facilitate the understanding of the text. Lastly, this study encounters that Luke 4:4 variants comes from secondary language manuscripts, Matthew 4:4 and Deuteronomy 8:3. Keywords: Luke 4:4, text criticism, Codex Sinaiticus, Codex Vaticanus, Codex Washingtonianus